Automatic Bandwidth Adjustment for Content Distribution in MPLS Networks. (7th February 2008) - Moltchanov, D.
Abstract : Aggregates of real-time traffic may experience changes in their statistical characteristics often manifesting non stationary behavior. In multi protocol label switching (MPLS) networks this type of the traffic is assigned constant amount of resources. This may result in ineffective usage of resources when the load is below than expected or inappropriate performance when the load is higher. In this paper we propose new algorithm for dynamic resource adaptation to temporarily changing traffic conditions. Assuming that network nodes may reallocate resources on-demand using automatic bandwidth adjustment capability of MPLS framework, the proposed algorithm, implemented at ingress MPLS nodes, dynamically decides which amount of resources is currently sufficient to handle arriving traffic with given performance metrics. This decision is then communicated to interior MPLS nodes along the label switched path. As a basic tool of the algorithm we use change-point statistical test that signals time instants at which statistical characteristics of traffic aggregates change. The major advantage of the proposed approach is that it is fully autonomous, that is, network nodes do not need any support from hosts in terms of resource reservation requests. The proposed algorithm is well suited for traffic patterns experiencing high variability, especially, for non stationary type of the traffic.